A process-performance coupled design method for hot-stamped tailor rolled blank structure. (July 2019) - Cheng, Wei; Zhang, Huile; Fu, Shan; Xie, Hui; Tang, Zhiwen; Zhu, Zhenglong
Abstract: Hot stamping and tailor rolled blank (TRB) technology has been increasingly used in the automotive industry for its distinct predominance in lightweight design. The hot-stamped TRB part's performance is closely related to the hot stamping process and thickness variation. It has been a challenging task to obtain optimal process parameters and thickness distributions for hot-stamped TRB parts, especially in crashworthiness design. To address this issue, a multi-objective reliability-based design optimization (MORBDO) method is presented for the crashworthiness design of a hot-stamped TRB part considering manufacturing effects. This method integrates the sequential coupling method, global sensitivity analysis (GSA), the nondominated sorting genetic algorithm II (NSGA-II) and Monte Carlo simulation (MCS). To map hot-stamping effects to the crashing model, a sequential coupling method is presented. Subsequently, GSA is conducted to calculate the sensitivity indicators using Sobol's approach to improve optimization efficiency. Finally, the NSGA-II combined with the MCS method is implemented to search for the optimal reliable scheme. The numerical results demonstrate the capability and efficiency of the proposed optimization method for achieving reliable designs for hot-stamped TRB parts. Furthermore, there exists a tradeoff between the hot-stamped part's performance and the desired reliability level. In summary, the proposed method not only significantly increases the crashworthiness and formability but also improves the reliability of the optimized design. Highlights: This is the first study to evaluate the performance of hot-stamped TRB structures with manufacturing effect. The proposed process-performance coupled method is proved effective for mapping hot-stamping result to crashing model. The crashing model with hot-stamping result has lower specific energy absorption and larger dynamic intrusion. A tradeoff should be made not only between crashworthiness and formability but also the reliability level and properties.